Antioxidant Activity of Coffee Components Influenced by Roast Degree and Preparation Method - Rafał Wołosiak; Paulina Pakosz; Beata Drużyńska; Monika Janowicz (Applied Sciences, 2023)
Coffee is of interest to consumers and researchers, mainly due to its stimulating properties and positive effects on the human body. Properties of coffee infusions depend on many factors and the most important ones include the roasting process and the brew preparation method. In this paper, we analyzed infusions prepared with the use of pressure methods (professional: espresso and consumer: moka pot brew), obtained from beans roasted to the medium and dark degree, with the aim of determining the share of individual groups of ingredients in the antioxidative properties of coffee. Tested infusions showed various characteristics that were partly related to different parameters of their preparation. In general, a greater amount of phenolic compounds was extracted in moka brews. Espresso, on the other hand, exhibited greater antioxidant activity per portion of the brew and a greater ability to quench free radicals. The degree of roasting had an uneven effect on the antioxidant activity of the brews, depending on the method and its mechanism of antioxidant action. The share of activity of the particular groups of antioxidants in overall activity varied between all methods; the most pronounced changes were observed in the espresso brews. The results indicate, however, that the activity of phenols and melanoidins is based on a mixed mechanism of antioxidant action, but in the case of the latter, the mechanism of hydrogen atom transfer may have an advantage.